A Multilevel Analysis of Economic Literacy Among International Students: Implications for an International Assessment of Heterogeneous Vulnerable Learner Groups - Reinhardt, Franziska; Zlatkin-Troitschanskaia, Olga; Happ , Roland; Nell-Müller, Sarah (Journal of International Students, 2021)
International student mobility has increased in the past years. The inclusion of a highly heterogeneous group of students requires updated recruitment and admission strategies. A particularly vulnerable group of international students are refugees, who have an exceptionally high risk of dropping out of their studies. We present an entrance assessment of incoming international students from 77 countries who are at the beginning of their studies in Germany. Based on this unique sample, we examine (i) whether there are systematic country-specific effects on the economic literacy of beginning students of business and economics and (ii) whether refugee students differ from the group of international students. The results show that refugee students have a higher level of economic literacy although their country-specific prerequisites are worse. Hence, the results highlight the high relevance of an international assessment of heterogeneous vulnerable learner groups to promote their integration into the increasingly internationalized higher education sector.